KUALITAS PERUMAHAN DI DESA MRANGGEN KECAMATAN SRUMBUNG KABUPATEN MAGELANG - Kurnianingrum, Ragil (Jurnal Geografi, 2016)
The aims of this research are: 1) Understanding peopleâs social and economy condition in MranggenVillage, 2) Measuring housing quality in Mranggen Village, 3) Understanding the relationship peopleâssocial and economy condition towards housig quality in Mranggen Village. Data technical analysis usedstatistic descriptive, scoring, independent difference experiment, and crosstab. The result of the research: 1)Kedungsari Orchard and Salamsari Orchard each of them has householdâs education rate and householdâsincome rate with good criteria. Most of householdâs in Orchard Kedungsari graduated Junior High School(40%), while in Orchard Salamsari most of graduated Senior High School (45%). peopleâs house most ofthem stand on heritable land, 2) Most of householdâs houses in Kedungsari Orchard and Salamsari Orchardinclude in good criteria, there are 70% in Orchard Kedungsari and 72,5% in Orchard Salamsari, 3) There isfound a significant relationship between householdâs education rate toward householdâs income, besidehouseholdâs income also has a relationship toward housing quality, but the status of land ownership has norelationship toward housing quality.